A Study of the evolution of prefixal verbs in Dibaji dialect from the perspective of grammaticalization - Havva Haj eidi; Gholam Reza Dinmohammadi (مطالعات زبانی و بلاغی)
The aim of the present study is to examine the historical evolution of the prefixal verbs in Dibaji dialect. One of the important factors in the evolution process of languages is grammaticalization, in which lexical categories become grammatical morphemes or grammatical categories become more restricted than before. The reverse process is called degrammaticalization.In the present article, we intend to examine the evolution of prefixal verbs in Dibaji dialect and find the answer to the question whether grammaticalization occurred during the change of the prefixal verbs of this dialect or these verbs were degrammaticalized. In order to answer this question, we examine the evolution of verbal prefixes and the formation of these prefixal verbs over time. Studying the ancient texts of Iranian languages, we indicate that the prefixes of these verbs were lexical items in the ancient period, which were decategorized and evolved into current forms by acquiring a grammatical role and changing into affixes. Then, we indicate that the degrammaticalization process has occurred by attaching verbal prefixes to simple verbs and the formation of prefixal verbs.In this research, more than 300 prefixal verbs were collected and analyzed in a descriptive, analytical and comparative way.